A Critical Review of Structural Topology Optimization Algorithms - Jiao Yuhang (E3S Web of Conferences)
In the past 30 years , the field of structural topology optimization has developed rapidly, and many representative algorithms such as homogenization algorithm, solid isotropic material with penalization algorithms and evolutionary structural optimization algorithms have emerged. In this paper, the above three representative algorithms’ principles and development history are briefly introduced. Secondly, with the classic example of long cantilever beams, the three methods are compared in all aspects of the optimisation process, and their similarities and differences in terms of optimisation objectives, constraints, and characteristics of the results are analysed. Finally, the above algorithms are summarized, and their advantages, disadvantages and applicable scenarios are listed, which will provide reference for future designers to a certain extent.